(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
Shallot is a spice vegetable that belongs to the allium group like onion, with a stronger aroma and appetising taste, but could leach during blanching. The effects of different magnetic field strengths (MFS) and pretreatment times (PT) on the quality of Pulsed Electromagnetic Field Treated Shallot Powder (PEMFT-SP) and the sensory properties of Smoked Meat (Soya) spiced with PEMFT-SP were evaluated. Shallot bulbs were treated at different MFS (8.00 to 24.00mT) and PT (5 to 25 minutes) using PEMF device. The treated samples were oven dried (at 60°C for 5 hrs) and then milled into powder. A control sample was produced by using blanching as pretreatment. Samples were analysed for chemical and sensory properties using standard methods. Chemical and organoleptic quality of PEMFT – SP were significantly varied with MFS and PT. Vitamin contents of PEMFT-SP had the highest retention at 24.00mT for 10 minutes. Mineral content of the SP samples was significantly higher than the control. Antioxidant capacity of the PEMFT-SP had the highest retention at 13.50mT for 20mins. Except for phytate, blanching as a pre-treatment was more effective than PEMF (8.00 to 30.00mT for 5 to 25mins) in the reduction of antinutritional properties. Sensory panellists judged the PEMFT-SP at MFS 24.00mT for 10 minutes to be of best acceptability. Therefore, pretreatment of SP with PEMF retained the vitamins, minerals and antioxidant content. However, studies on optimization of MFS and PT for PEMF-treatment of shallot or similar species are recommended.